On Selection of Access Network Technology by using Different Metrics in a Fixed Network: A Technology Investment and Cost Approach - Basic, Almir; Begovic, Alen; Goran, Nermin (Proceedings Elmar ... (Online), 2024)
This paper presents present an example of the method of selecting an optimal model of fixed access network and compare various well-known access network technology choices in heterogeneous environment, in order to selecting an optimal solution. Architecture scenarios and technologies used for experimenting are P2P (Point to Point)) based on Ethernet, P2MP (Point to MultiPoint) based on GPON (Gigabit Passive Optical Network) technology and FTTB/C (Fibre to The Building/Cabinet) based on VDSL technology. After short reminder of FOAN (Fibre Optics Access Network) architectures, topologies and technologies and brief comparisons of P2P vs. GPON and FTTH (Fibre to The Home) vs. FTTB, the sample areas, which are subject of analysis are described in detail. A comparison of proposed solutions in four chosen areas is shown.